Influence of sampling procedure, sampling location and skin contamination on skatole and indole concentrations in adipose tissue of pigs. (January 2016) - Wesoly, Raffael; Stefanski, Volker; Weiler, Ulrike
Abstract: Skatole leads to off-odor in pork and is influenced by several factors such as sex and management conditions of pigs, but the causal relationships have not yet been clarified. In the present study, physiological skatole concentrations along the carcass were monitored and the transdermal diffusion of skatole was experimentally studied with skatole-spiked feces. Additionally, the impact of different biopsy techniques on skatole in fat and blood was studied. Monitoring of skatole along the carcass revealed higher skatole concentrations in the belly than in dorsal cuts. Topical application of spiked feces increased skatole in fat strictly at the application site. In contrast to punch biopsies, surgical biopsies significantly affected skatole and cortisol levels in blood, but not in fat. We conclude that biopsies for skatole measurements should be taken without anesthesia from the dorsal side of the animals. Fecal contaminations on the ventral side are not likely to influence overall concentrations. Highlights: Skatole concentrations are similar along the dorsal part of carcass. Skatole concetrations are higher in the belly than in dorsal samples. Transdermal diffusion of skatole into adipose tissue is limited. Similar fluctuations of cortisol and skatole in blood after surgical biopsies. Punch biopsies do not affect levels of cortisol or skatole in blood.